Survival and Witness at Europe's Border : The Afterlives of a Disaster - Horsti, Karina (Book collections on Project MUSE., 2023)
"Through the analysis of representation and memorialization, this book examines the afterlives of a deadly migrant shipwreck in Italy in 2013 among different witnesses: Eritrean survivors, families of victims, Eritrean diaspora, rescuers and locals in Lampedusa and Sicily, and citizens across Europe"--